2019
DOI: 10.25083/rbl/24.2/360.365
|View full text |Cite
|
Sign up to set email alerts
|

The utility of Narrow Band Imaging in obtaining disease free resection margins during endo-scopic surgery of the larynx

Abstract: Narrow Band Imaging (NBI) is an optical method that helps the surgeon visualize lesions that are not always visible under white light endoscopy. First the method was used in gastroenterology, almost 10 years ago, with great success. Four years ago the optical method was transferred in the ENT (Ear Nose Throat) field and now it is available on fiber optic and rigid endoscopes. The technological advancement, the introduction of new video chips capable to produce HDTV (high definition TV) images offered the surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Beyond the diagnostic phase, NBI holds a lot of promise for achieving more accurate margin delineation during TLM for early glottic cancer ( Table 2 and Table 3 ) [ 42 ]. It has been reported that NBI was able to, statistically, significantly reduce [ 3 , 18 , 19 , 23 , 25 ], or completely prevent, the occurrence of positive superficial margins [ 20 , 21 ]. Overall, two studies reported the detection of additional lesions that were not seen with WL alone [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the diagnostic phase, NBI holds a lot of promise for achieving more accurate margin delineation during TLM for early glottic cancer ( Table 2 and Table 3 ) [ 42 ]. It has been reported that NBI was able to, statistically, significantly reduce [ 3 , 18 , 19 , 23 , 25 ], or completely prevent, the occurrence of positive superficial margins [ 20 , 21 ]. Overall, two studies reported the detection of additional lesions that were not seen with WL alone [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The basic principle of narrowband imaging technology is to narrow the white light wavelength of the xenon lamp into narrowband light waves of blue (wavelength 415 nm), green (wavelength 540 nm), and red (wavelength 600 nm) through special filters, mainly emphasizing blue light [ 1 ]. This narrowband light wave dominated by blue light has weak penetrating power and shallow irradiation depth and can only reach the surface of the tissue, thereby increasing the contrast and clarity of the mucosa, so it can clearly display the mucosal surface structure and gland duct opening shape [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%